Description of Self-Forgiveness in Correctional Inmates (WBP) in Class IIA Kupang Prison - Tahu, Sebastianus Kurniadi; Bina, Maria Y; Jesus Pereira, Laura De (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background : Inmates will go through many life processes in prison, inmates will experience symptoms of low forgiveness in themselves, namely they often experience anxiety, harbor feelings of guilt, desire for revenge, unstable emotions, feel hurt, and find it difficult to accept reality, where they think with their condition in prison is the result of mistakes because of themselves, others or a situation. Objective: This study was to determine the description of self-forgiveness in inmates in prisons class IIA Kupang. Methods: This research is a quantitative research using a descriptive design. The sample in this study was the Correctional Inmates (WBP) in the Class IIA Kupang prison totaling 218 people who were selected using purposive sampling technique. This research instrument uses a self-forgiveness scale questionnaire. Results: it was found that most of the inmates in Class IIA Kupang prisons were in the high self-forgiveness category, as many as 105 inmates (48.2%). Suggestion: It is recommended for Correctional Inmates (WBP) in Class IIA Kupang Prison to increase positive attitudes and knowledge about Self-Forgivenes.